1982
DOI: 10.1038/bjc.1982.118
|View full text |Cite
|
Sign up to set email alerts
|

Increased survival of cancer-bearing mice treated with inhibitors of prostaglandin synthesis alone or with chemotherapy

Abstract: Summary.-In mice with a transplantable mammary carcinoma, treatment with the prostaglandin-synthesis inhibitors flurbiprofen or indomethacin produced various beneficial effects. Survival time after excision of the transplanted tumour was increased, particularly when the drugs were given with the chemotherapeutic agents methrotrexate and melphalan, and there were more disease-free survivors. The combined treatment with flurbiprofen also gave less tumour recurrence at the excision site. Flurbiprofen did not seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Mice with advanced carcinomatosis, or those who survived for the duration of the experiment, were killed humanely to prevent suffering. From previous experience, the mice killed humanely because of metastasis would have died within 24h (see Bennett et al, 1982). Occasionally mice that were not in distress in the evening died overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice with advanced carcinomatosis, or those who survived for the duration of the experiment, were killed humanely to prevent suffering. From previous experience, the mice killed humanely because of metastasis would have died within 24h (see Bennett et al, 1982). Occasionally mice that were not in distress in the evening died overnight.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, several groups have found that PG synthesis inhibitors reduce mouse tumour weight (Hial et al, 1976;Bennett et al, 1978Bennett et al, , 1979Bennett et al, , 1982Lynch et al, 1978;Lynch & Salomon, 1979;Trevisani et al, 1980), and increase host survival (Lynch et al, 1978;Bennett et al, 1978Bennett et al, , 1979Bennett et al, , 1982Trevisani et al, 1980). In a few studies PG synthesis inhibitors were not of value, indicating that different tumour types may vary in their response (see Bennett, 1982).…”
mentioning
confidence: 99%
“…1 modified diet and had free access to water. On day 0, female WHT/Ht mice were injected s.c. into the left flank with 106 NC carcinoma cells prepared as described previously (Bennett et al, 1979(Bennett et al, , 1982 In 4 other experiments, each with 10-15 female mice/group, nafazatrom 1 or 2mgkg-1 was given daily by mouth in 0.1 ml 50% syrup. Treatment started on the day prior to tumour transplantation and continued until death or the end of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…(1982) found that tumour cells which produced highest amounts of TXA2 were most metastatic in mice. However, it is not known to what extent this applies to other tumours, and no studies relating to Drugs that inhibit cyclo-oxygenase usually reduce the size of NC tumours, and prolong host survival when given alone or with the cytotoxic drugs methotrexate and melphalan (Bennett et al, 1979(Bennett et al, , 1982. Cyclo-oxygenase inhibitors reduce both thromboxane and prostaglandin formation, but it is not known if the effect on thromboxane production contributes to the effects of indomethacin and flurbiprofen on tumour size and mouse survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation